Clinician-friendly lower extremity physical performance tests in athletes: a systematic review of measurement properties and correlation with injury. Part 2—the tests for the hip, thigh, foot and ankle including the star excursion balance test. Issue 10 (22nd January 2015) - Hegedus, Eric J; McDonough, Suzanne M; Bleakley, Chris; Baxter, David; Cook, Chad E
Abstract : Objective: To review the quality of literature and measurement properties of physical performance tests (PPTs) of the lower extremity in athletes. Methods: Using the PICOS method we established our research question as to whether individual PPTs of the lower extremity have any relationship to injury in competitive athletes ages 12 years to adult (no limit). A search strategy was constructed by combining the terms 'lower extremity' and synonyms for 'performance test' and names of performance tests with variants of the term 'athlete'. After examining the knee in part 1 of this 2 part series, the current report focuses on findings in the rest of the lower extremity. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed and the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) checklist was used to critique the methodological quality of each paper. A second measure was used to analyse the quality of the measurement properties of each test. Results: Thirty-one articles examined the measurement properties of 14 PPTs pertaining to the lower extremity. The terminology used to name and describe the tests and methodology by which the tests were conducted was inconsistent. The star excursion balance test performed in three directions (anterior, posteromedial, and posterolateral) appears to be the only test to be associated with increased injury risk. There is moderate evidence that the one leg hop for distance and the hexagon hop can distinguish between normal and unstable ankles. There is also moderate evidence that the medial hop can distinguish between painful and normal hips in dancers. Conclusions: Currently, there is relatively limited research-backed information on PPTs of the lower extremity in athletes. We would suggest convening an international consortium comprised of experts in sports to standardise the descriptions and methodologies, and to set forth a research agenda to establish definitively the measurement properties of the most common PPTs.